Budaya Ritual Topo Ngeluwang Di Petilasan Sunan Kalijaga Bukit Surowiti Kabupaten Gresik - Masrul Anam (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
This study aims to find out how the ritual procession in Surowiti Hill is and what is the purpose of performing the ritual. In the Javanese belief, topo ngeluwang has become a ritual’s belief, for people who want to get abundant gift, high position, or other blessings. The Sunan Kalijaga petilasan site is located in the village of Surowiti, Panceng subdistrict, Gresik City, which is a special place to perform the topo ngeluwang ritual. From the research, the result shows that this topo is very frightening and requires a very high level of courage. Topo ngeluwang is said to be a way to get supernatural powers and get rid of something. Topo ngeluwang is meditating by being buried in a cemetery or a very quiet place. After a person performs austerity, usually, he will be able to see unseen things such as spirits, jinn and so on.